Handbook of spine surgery - Baaj, Ali A.; Mummaneni, Praveen V.; Uribe, Juan S.; Vaccaro, Alexander R. (Thieme, 2016)
Handbook of Spine Surgery is authoritative, concise, and portable--designed for use in a fast-paced clinical setting. Its coverage of both principles and techniques of contemporary spine surgery--including anatomy, pathology, procedures, and instrumentation--makes it highly useful as a refresher before surgery, an easily digestible study guide, or a daily companion for physicians caring for patients with spinal disorders.